A high-conductivity automobile wiring harness and preparation method thereof

By performing composite oxide powder and surface borication treatment on pure copper powder and added to copper melt to cast, the problems of automotive wire harness wire strength and conductivity are solved, and the preparation of automotive wire harness wires with high conductivity and high tensile strength is achieved .

CN116403773BActive Publication Date: 2025-01-10HUNAN YILISHENG ELECTRONICS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310381132.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-01-10
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

Existing automotive wiring harness wires are prone to plastic deformation when subjected to stress, affecting signal transmission, and adding alloy elements to increase strength will lead to a decrease in conductivity, which cannot meet the requirements of high conductivity and high strength.

Method used

Pure copper powder is used to form composite oxide powder after multiple soaking, drying and calcining, then undergo reduction and surface borylation, and added to copper melt for magnetic stirring and casting to form a high-conductivity automotive wire harness wire.

Benefits of technology

The tensile strength of the automotive wiring harness wire is improved, the service life is extended, and the high conductivity is maintained, avoiding significant reduction in the electrical properties of the wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116403773B_ABST
    Figure CN116403773B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-conductivity automotive wiring harness wire, comprising the following steps: (1) obtaining composite oxide powder on the surface of pure copper by thermal decomposition; (2) reducing the copper-based composite oxide powder in hydrogen to obtain copper-based powder; (3) surface boronizing the copper-based powder to obtain copper-based powder after surface boronization; (4) melting a pure copper block into a melt under a vacuum environment, magnetically stirring the melt, adding the boronized copper-based powder to the melt during the stirring process, casting, and obtaining a copper wire material; (5) heating the copper wire material to 950°C for insulation, then drawing to form a copper wire, and then aging treatment at 450±10°C for 2-4h under a vacuum environment, cooling to room temperature with the furnace, and obtaining a high-conductivity automotive wiring harness wire. The automotive wiring harness wire prepared by the method of the invention has a high tensile strength, improves the service life of the wiring harness wire, has a small effect on the conductivity of the copper alloy wire, and does not cause a significant reduction in the electrical properties of the wire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile wiring harness materials, and in particular to an automobile wiring harness with high conductivity and a preparation method thereof. Background Art

[0002] The automotive wiring harness is the main body of automotive signal transmission and plays a vital role in automotive design and use. The wiring harness is mainly composed of wires and cables, metal contacts, connectors, and wrapping fixtures. The automotive wiring harness connects various electronic components on the car. It must not only be able to accurately transmit various signals, but also ensure the reliability of the connection circuit. Copper alloy wire has excellent electrical conductivity, thermal conductivity, ductility and corrosion resistance, and is widely used in wire and cable assemblies of automotive wiring harnesses. However, copper has relatively low strength and is prone to plastic deformation under stress, affecting normal signal transmission. However, if alloy elements are added, although the strength of copper can be improved to a certain extent, the deterioration of copper conductivity is more serious, and it cannot be used in the manufacture of automotive wiring harnesses. Summary of the invention

[0003] To this end, the present invention provides a method for preparing a high-conductivity automotive wiring harness wire, comprising the following steps:

[0004] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in turn, and dried for standby use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, and the dried pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 to 2 minutes, and then the pure copper powder is taken out, dried at 100±5°C for 10 minutes, and then calcined in a muffle furnace at 400°C for 15 minutes, and then immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol again for 1 to 2 minutes after calcination, and after immersion, the pure copper powder is taken out, dried at 100±5°C for 10 minutes, and then calcined in a muffle furnace at 400°C for 15 minutes, and the immersion, drying and calcination processes are repeated for more than 15 groups, and the last time, the pure copper powder is calcined in a muffle furnace at 400°C for 1 hour, and then air-cooled to room temperature to obtain a composite oxide powder;

[0005] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for more than 1 hour to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0006] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboron on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glow heating, and when the furnace temperature rises to 100°C, fill the furnace with hydrogen to a pressure of 2 00Pa, and then increase the duty cycle to raise the temperature without arc discharge; when the temperature in the furnace rises to 250°C, fill the furnace with argon and hydrogen at the same time to make the pressure in the furnace 400Pa, and then fix the pressure unchanged, adjust the set voltage to 750V, set the temperature to 450°C, start timing after reaching the set temperature, keep warm for 6 to 8 hours, turn off the power after the insulation is over, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then balance the air pressure inside and outside the furnace, open the furnace cover, take out the powder, and obtain the copper-based powder after surface boronization;

[0007] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt the melt, performing magnetic stirring on the melt, adding the boronized copper-based powder to the melt during the stirring process, and continuing to stir at 1300° C. for 5 to 8 minutes after the addition is completed, and then cooling to 1150° C. for casting to obtain a copper conductor material;

[0008] (5) The copper wire material is heated to 950° C. and kept at this temperature for 40 to 50 minutes, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 2 to 4 hours in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

[0009] Furthermore, in the step (1), in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol, the concentration of cerium trichloride is 8-12 g / L, the concentration of zinc chloride is 20-26 g / L, the concentration of ruthenium trichloride hydrate is 3-5 g / L, the volume percentage of ethylene glycol is 10%-20%, and the solvent is water.

[0010] Furthermore, in the step (3), the volume ratio of argon and hydrogen is argon:hydrogen=2-3:600.

[0011] Furthermore, the mass ratio of the boronized copper-based powder added to the melt is boronized copper-based powder / melt=0.1% to 0.2%.

[0012] The beneficial effects of the present invention are as follows: the automotive wiring harness wire prepared by the method of the present invention has high tensile strength, improves the service life of the wiring harness wire, has little effect on the conductivity of the copper alloy wire, and does not cause a significant reduction in the electrical performance of the wire. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The following is a comparison chart of the tensile strength and electrical conductivity of automotive wiring harness wires prepared by the methods described in various embodiments and comparative examples. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the embodiments.

[0015] Example 1

[0016] A method for preparing a high-conductivity automotive wiring harness wire comprises the following steps:

[0017] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in sequence, and dried for use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 8 g / L, the concentration of zinc chloride is 20 g / L, the concentration of ruthenium trichloride hydrate is 3 g / L, the volume percentage of ethylene glycol is 10%, and the solvent is water; the dried pure copper powder is immersed in the cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol composite aqueous solution; The copper powder is immersed in the composite aqueous solution for 1 min, then the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. After calcination, it is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min again. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. The immersion, drying and calcination processes are repeated for 15 groups in total. The last time, it is calcined in a muffle furnace at 400°C for 1 hour, and then air-cooled to room temperature to obtain a composite oxide powder.

[0018] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0019] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboric acid on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glowing and heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then turn on ... Under the premise of arc discharge, the duty cycle is increased to raise the temperature; when the temperature in the furnace rises to 250°C, argon and hydrogen are simultaneously filled into the furnace to make the pressure in the furnace 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 2:600; then the pressure is fixed unchanged, the set voltage is adjusted to 750V, the set temperature is 450°C, and the timing is started after reaching the set temperature, and the temperature is kept for 6 hours. After the insulation is completed, the power is turned off, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then the air pressure inside and outside the furnace is balanced, the furnace cover is opened, and the powder is taken out to obtain the copper-based powder after surface boronization;

[0020] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, and magnetically stirring the melt. During the stirring process, the boronized copper-based powder is added to the melt, and the mass ratio of the boronized copper-based powder added is the boronized copper-based powder / melt = 0.1%; after the addition is completed, the temperature is kept at 1300° C. and stirred for 5 minutes, and then the temperature is lowered to 1150° C. for casting to obtain a copper conductor material;

[0021] (5) The copper wire material is heated to 950° C. and kept at this temperature for 40 minutes, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 2 hours in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

[0022] Example 2

[0023] A method for preparing a high-conductivity automotive wiring harness wire comprises the following steps:

[0024] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in sequence, and dried for later use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 10 g / L, the concentration of zinc chloride is 22 g / L, the concentration of ruthenium trichloride hydrate is 4 g / L, the volume percentage of ethylene glycol is 10%, and the solvent is water; the dried pure copper powder is immersed in the cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol. The pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min, and then the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. After calcination, the pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. The immersion, drying and calcination processes are repeated for 15 groups. The last time, the pure copper powder is calcined in a muffle furnace at 400°C for 1 h, and then air-cooled to room temperature to obtain a composite oxide powder.

[0025] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0026] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboric acid on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glowing and heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then turn on ... Under the premise of arc discharge, the duty cycle is increased to raise the temperature; when the temperature in the furnace rises to 250°C, argon and hydrogen are simultaneously filled into the furnace to make the pressure in the furnace 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 2:600; then the pressure is fixed unchanged, the set voltage is adjusted to 750V, the set temperature is 450°C, and the timing is started after reaching the set temperature, and the temperature is kept for 7h. After the heat preservation is completed, the power is turned off, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then the pressure inside and outside the furnace is balanced, the furnace cover is opened, and the powder is taken out to obtain the copper-based powder after surface boronization;

[0027] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, and magnetically stirring the melt. During the stirring process, the boronized copper-based powder is added to the melt, and the mass ratio of the boronized copper-based powder added is the boronized copper-based powder / melt = 0.1%; after the addition is completed, the temperature is kept at 1300° C. and stirred for 5 minutes, and then the temperature is lowered to 1150° C. for casting to obtain a copper conductor material;

[0028] (5) The copper wire material is heated to 950° C. and kept at this temperature for 40 minutes, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 3 hours in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

[0029] Example 3

[0030] A method for preparing a high-conductivity automotive wiring harness wire comprises the following steps:

[0031] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in sequence, and dried for standby use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 10 g / L, the concentration of zinc chloride is 24 g / L, the concentration of ruthenium trichloride hydrate is 4 g / L, the volume percentage of ethylene glycol is 20%, and the solvent is water; the dried pure copper powder is immersed in the cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol. The pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min, and then the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. After calcination, the pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. The immersion, drying and calcination processes are repeated for 15 groups. The last time, the pure copper powder is calcined in a muffle furnace at 400°C for 1 h, and then air-cooled to room temperature to obtain a composite oxide powder.

[0032] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0033] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboric acid on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glowing and heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then turn on ... Under the premise of arc discharge, the duty cycle is increased to raise the temperature; when the temperature in the furnace rises to 250°C, argon and hydrogen are simultaneously filled into the furnace to make the pressure in the furnace 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 3:600; then the pressure is fixed unchanged, the set voltage is adjusted to 750V, the set temperature is 450°C, and the timing is started after reaching the set temperature, and the temperature is kept for 7h. After the heat preservation is completed, the power is turned off, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then the air pressure inside and outside the furnace is balanced, the furnace cover is opened, and the powder is taken out to obtain the copper-based powder after surface boronization;

[0034] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, and magnetically stirring the melt. During the stirring process, the boronized copper-based powder is added to the melt, and the mass ratio of the boronized copper-based powder added is the boronized copper-based powder / melt = 0.2%; after the addition is completed, the temperature is kept at 1300° C. and stirred for 5 minutes, and then the temperature is lowered to 1150° C. for casting to obtain a copper conductor material;

[0035] (5) The copper wire material is heated to 950° C. and kept at this temperature for 50 min, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 3 h in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

[0036] Example 4

[0037] A method for preparing a high-conductivity automotive wiring harness wire comprises the following steps:

[0038] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in sequence, and dried for later use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 12 g / L, the concentration of zinc chloride is 26 g / L, the concentration of ruthenium trichloride hydrate is 5 g / L, the volume percentage of ethylene glycol is 20%, and the solvent is water; the dried pure copper powder is immersed in the cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol. The pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min, and then the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. After calcination, the pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. The immersion, drying and calcination processes are repeated for 15 groups. The last time, the pure copper powder is calcined in a muffle furnace at 400°C for 1 h, and then air-cooled to room temperature to obtain a composite oxide powder.

[0039] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0040] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboric acid on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glowing and heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then turn on ... Under the premise of arc discharge, the duty cycle is increased to raise the temperature; when the temperature in the furnace rises to 250°C, argon and hydrogen are simultaneously filled into the furnace to make the pressure in the furnace 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 3:600; then the pressure is fixed unchanged, the set voltage is adjusted to 750V, the set temperature is 450°C, and the timing is started after reaching the set temperature, and the temperature is kept for 8 hours. After the insulation is completed, the power is turned off, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then the pressure inside and outside the furnace is balanced, the furnace cover is opened, and the powder is taken out to obtain the copper-based powder after surface boronization;

[0041] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, and magnetically stirring the melt. During the stirring process, the boronized copper-based powder is added to the melt, and the mass ratio of the boronized copper-based powder added is the boronized copper-based powder / melt = 0.2%; after the addition is completed, the temperature is kept at 1300° C. and stirred for 5 minutes, and then the temperature is lowered to 1150° C. for casting to obtain a copper conductor material;

[0042] (5) The copper wire material is heated to 950° C. and kept at this temperature for 50 min, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 4 h in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

[0043] Comparative Example 1

[0044] A comparative method for preparing a wire harness for an automobile comprises the following steps:

[0045] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in turn, and dried for later use; a composite aqueous solution of cerium trichloride, zinc chloride and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 10 g / L, the concentration of zinc chloride is 24 g / L, the volume percentage of ethylene glycol is 20%, and the solvent is water; the dried pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride and ethylene glycol for 1 minute, and then the pure copper powder is added to the sieved powder. The copper powder is taken out, dried at 100±5°C for 10 minutes, and then placed in a muffle furnace at 400°C for calcination for 15 minutes. After calcination, it is immersed in the composite aqueous solution of cerium trichloride, zinc chloride and ethylene glycol for 1 minute. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 minutes, and then placed in a muffle furnace at 400°C for calcination for 15 minutes. The immersion, drying and calcination processes are repeated for 15 groups. The last time, it is placed in a muffle furnace at 400°C for calcination for 1 hour, and then air-cooled to room temperature to obtain a composite oxide powder;

[0046] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0047] (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboric acid on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50 Pa, turn on the voltage, set the voltage to 700 V, adjust the duty cycle to start glowing and heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then turn on ... Under the premise of arc discharge, the duty cycle is increased to raise the temperature; when the temperature in the furnace rises to 250°C, argon and hydrogen are simultaneously filled into the furnace to make the pressure in the furnace 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 3:600; then the pressure is fixed unchanged, the set voltage is adjusted to 750V, the set temperature is 450°C, and the timing is started after reaching the set temperature, and the temperature is kept for 7h. After the heat preservation is completed, the power is turned off, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then the air pressure inside and outside the furnace is balanced, the furnace cover is opened, and the powder is taken out to obtain the copper-based powder after surface boronization;

[0048] (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, and magnetically stirring the melt. During the stirring process, the boronized copper-based powder is added to the melt, and the mass ratio of the boronized copper-based powder added is the boronized copper-based powder / melt = 0.2%; after the addition is completed, the temperature is kept at 1300° C. and stirred for 5 minutes, and then the temperature is lowered to 1150° C. for casting to obtain a copper conductor material;

[0049] (5) The copper wire material is heated to 950° C. and kept at this temperature for 50 min, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 3 h in a vacuum environment, and then cooled to room temperature in the furnace to obtain the automotive wiring harness wire described in this comparative example.

[0050] Comparative Example 2

[0051] A comparative method for preparing a wire harness for an automobile comprises the following steps:

[0052] (1) Surface boronization: Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected and spread on a stainless steel plate. The stainless steel plate is placed on the cathode plate of a low-temperature glow plasma infiltration furnace. The stainless steel plate and the cathode plate are separated by a ceramic pad. The stainless steel plate is covered with a copper mesh, on which boron iron is placed, and the bottom of the copper mesh is in contact with the cathode plate. The low-temperature glow plasma infiltration furnace is then covered, and the furnace is evacuated to below 50 Pa. The voltage is then turned on and set to 700 V. The duty cycle is adjusted to start heating. When the temperature in the furnace rises to 100°C, hydrogen is filled into the furnace to a pressure of 200Pa, then increase the duty cycle to raise the temperature without arc discharge; when the temperature in the furnace rises to 250°C, fill the furnace with argon and hydrogen at the same time so that the pressure in the furnace is 400Pa, and the volume ratio of argon and hydrogen is argon: hydrogen = 3:600; then fix the pressure unchanged, adjust the set voltage to 750V, set the temperature to 450°C, start timing after reaching the set temperature, keep warm for 7h, turn off the power after the insulation is over, and the powder is cooled to room temperature in the hydrogen atmosphere in the furnace, then balance the pressure inside and outside the furnace, open the furnace cover, take out the powder, and obtain the copper powder after surface boronization;

[0053] (2) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, subjecting the melt to magnetic stirring, and adding the boronized copper powder to the melt during the stirring process, wherein the mass ratio of the boronized copper powder added is boronized copper powder / melt=0.2%; after the addition is completed, the mixture is kept stirred at 1300° C. for 5 minutes, and then cooled to 1150° C. for casting to obtain a copper conductor material;

[0054] (3) The copper wire material is heated to 950° C. and kept at this temperature for 50 min, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 3 h in a vacuum environment, and then cooled to room temperature in the furnace to obtain the automotive wiring harness wire described in this comparative example.

[0055] Comparative Example 3

[0056] A comparative method for preparing a wire harness for an automobile comprises the following steps:

[0057] (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in sequence, and dried for standby use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, wherein the concentration of cerium trichloride is 10 g / L, the concentration of zinc chloride is 24 g / L, the concentration of ruthenium trichloride hydrate is 4 g / L, the volume percentage of ethylene glycol is 20%, and the solvent is water; the dried pure copper powder is immersed in the cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol. The pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min, and then the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. After calcination, the pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 min. After immersion, the pure copper powder is taken out, dried at 100±5°C for 10 min, and then calcined in a muffle furnace at 400°C for 15 min. The immersion, drying and calcination processes are repeated for 15 groups. The last time, the pure copper powder is calcined in a muffle furnace at 400°C for 1 h, and then air-cooled to room temperature to obtain a composite oxide powder.

[0058] (2) heating the copper-based composite oxide powder to 450±10° C. in a hydrogen atmosphere for 1 h to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder;

[0059] (3) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt into a melt, performing magnetic stirring on the melt, and adding the copper-based powder to the melt during the stirring process, wherein the mass ratio of the copper-based powder added is copper-based powder / melt=0.2%; after the addition is completed, the mixture is kept stirred at 1300° C. for 5 minutes, and then cooled to 1150° C. for casting to obtain a copper conductor material;

[0060] (4) The copper wire material is heated to 950° C. and kept at this temperature for 50 min, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 3 h in a vacuum environment, and then cooled to room temperature in the furnace to obtain the automotive wiring harness wire described in this comparative example.

[0061] Example 5

[0062] According to the requirements of national standard GB / T228-2002, the tensile strength of the automotive wiring harness wires prepared by the methods described in the above embodiments and comparative examples at room temperature was tested respectively; the electrical conductivity of the automotive wiring harness wires prepared by the methods described in the above embodiments and comparative examples at room temperature was tested using a digital metal conductivity meter. The results are as follows: Figure 1 shown.

[0063] Depend on Figure 1It can be seen that the automotive wiring harness wire prepared by the method of the present invention has a high tensile strength, improves the service life of the wiring harness wire, and has a small effect on the conductivity of the copper alloy wire, and does not cause a significant reduction in the electrical properties of the wire. Comparative Example 3 and each comparative example show that the present invention generates a composite layer on the surface of the copper powder in advance, and then adds it to the copper melt after surface boronization, and the mechanical properties of the copper wire obtained by casting are significantly improved. This may be because the obtained copper-based powder acts as a site for non-uniform nucleation during the casting process, greatly improving the formation rate of the crystal nucleus, and then refining the grain size inside the copper casting, which plays a role in fine grain strengthening. The powder particles uniformly distributed in the matrix in the cooled casting further play a role in hindering the movement of dislocations during the deformation process, showing a second phase strengthening effect. Therefore, the tensile strength of the copper wire is improved as a whole. On the one hand, adding rare earth elements cerium and ruthenium to copper-based powder can improve the morphology of copper-based powder and its dispersibility in the melt, prevent powder particles from agglomerating, and increase the surface area of ​​powder particles; on the other hand, surface boronization can improve the wettability of powder and melt, reduce the holes and microcracks between the two phases in the casting, thereby improving the casting defects of the casting from two aspects and improving the strength of the copper wire.

[0064] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a high-conductivity automotive wiring harness conductor, characterized in that: The steps include: (1) Pure copper powder is passed through a 2000 mesh sieve, and the sieved powder is collected. The sieved powder is washed with acetone and deionized water in turn, and dried for use; a composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol is prepared, and the dried pure copper powder is immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol for 1 to 2 minutes, and then the pure copper powder is taken out, dried at 100±5°C for 10 minutes, and then calcined in a muffle furnace at 400°C for 15 minutes, and then immersed in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol again for 1 to 2 minutes after calcination, and after immersion, the pure copper powder is taken out, dried at 100±5°C for 10 minutes, and then calcined in a muffle furnace at 400°C for 15 minutes, and the immersion, drying and calcination processes are repeated for more than 15 groups, and the last calcination is placed in a muffle furnace at 400°C for 1 hour, and then air-cooled to room temperature to obtain a composite oxide powder; (2) heating the composite oxide powder to 450±10° C. in a hydrogen atmosphere for more than 1 hour to perform a reduction reaction, and then cooling to room temperature in a hydrogen atmosphere to obtain a copper-based powder; (3) Surface boronization: Spread the copper-based powder on a stainless steel plate, place the stainless steel plate on the cathode plate of a low-temperature glow plasma infiltration furnace, separate the stainless steel plate and the cathode plate with a ceramic pad, cover the stainless steel plate with a copper mesh, place ferroboron on the copper mesh, and the bottom of the copper mesh is in contact with the cathode plate; then close the low-temperature glow plasma infiltration furnace, evacuate the furnace to below 50Pa, turn on the voltage, set the voltage to 700V, adjust the duty cycle to start glow heating, and when the temperature in the furnace rises to 100°C, fill the furnace with hydrogen to a pressure of 200 Pa, and then increase the duty cycle to raise the temperature without arc discharge; when the temperature in the furnace rises to 250°C, fill the furnace with argon and hydrogen at the same time to make the pressure in the furnace 400Pa, and then fix the pressure unchanged, adjust the set voltage to 750V, set the temperature to 450°C, start timing after reaching the set temperature, keep warm for 6 to 8 hours, turn off the power after the insulation is completed, and the copper-based powder is cooled to room temperature in the hydrogen atmosphere in the furnace, and then balance the air pressure inside and outside the furnace, open the furnace cover, take out the powder, and obtain the copper-based powder after surface boronization; (4) heating a pure copper block to 1300° C. in a vacuum induction melting furnace under a vacuum environment to melt the melt, performing magnetic stirring on the melt, adding the boronized copper-based powder to the melt during the stirring process, and continuing to stir at 1300° C. for 5 to 8 minutes after the addition is completed, and then cooling to 1150° C. for casting to obtain a copper conductor material; (5) The copper wire material is heated to 950° C. and kept at this temperature for 40 to 50 minutes, then air-cooled to room temperature, the surface oxide scale is removed, and the copper wire is drawn to form a copper wire. The copper wire is then aged at 450±10° C. for 2 to 4 hours in a vacuum environment, and then cooled to room temperature in the furnace to obtain a high-conductivity automotive wiring harness wire.

2. The method for preparing a high-conductivity automotive wiring harness conductor according to claim 1, characterized in that: In the step (1), in the composite aqueous solution of cerium trichloride, zinc chloride, ruthenium trichloride hydrate and ethylene glycol, the concentration of cerium trichloride is 8-12 g / L, the concentration of zinc chloride is 20-26 g / L, the concentration of ruthenium trichloride hydrate is 3-5 g / L, the volume percentage of ethylene glycol is 10%-20%, and the solvent is water.

3. The method for preparing a high-conductivity automotive wiring harness conductor according to claim 1, characterized in that: In the step (3), the volume ratio of argon and hydrogen is argon:hydrogen=2-3:

600.

4. The method for preparing a high-conductivity automotive wiring harness conductor according to claim 1, characterized in that: The mass ratio of the boronized copper-based powder added to the melt is boronized copper-based powder / melt=0.1% to 0.2%.

Citation Information

Patent Citations

  • Making method of highly conductive copper alloy wire or automobile generator

    CN104046832A

  • Preparation method of high heat-conducting copper alloy wire for automobile wire harness

    CN104152728A